ANALYSIS OF PUBLIC SATISFACTION INDEX FOR ROAD PUBLIC SERVICES - hakim, agus lukman; Sanjaya, Natta; Hanifah, Hanifah; Yuniar, Siti (Jurnal Sosial Humaniora, 2023)
One of the government’s duties is to provide optimal public services for the community. To measure the level of public satisfaction with public services, an evaluation of the quality of public service delivery is needed, one of which is the highway which is under the authority of the PUPR Office of Banten Province. This study used a quantitative approach with respondents being provincial road users. with a total of 265 respondents, divided into 26 Provincial Roads in the Serang and Cilegon areas. The sampling technique used was purposive sampling with a combination of accidental sampling techniques. The results showed that the Importance Performance Analysis (IPA) method obtained the results from 29 questions, of which 5 questions were in quadrant I (High Interest, Low Satisfaction), Whereas 15 questions are in quadrant II (High Interest, High Satisfaction), while 5 questions are in quadrant III (Low Interest, Low Satisfaction) and there are 4 questions in quadrant IV (Low Interest, High Satisfaction). 3. Based on the analysis of the Customer Statistics Index (CSI), the results of the CSI Customer Statistics Index (CSI) were 74.75%.This shows that people who use provincial road services in the Primary Collector Area (WKP) II (Serang-Cilegon) feel satisfied.